Distribution of sounds and call types across each female’s record. - Audra E. Ames (11349386); Susanna B. Blackwell (10013873); Outi M. Tervo (10013864); Mads Peter Heide-Jørgensen (7869812) (2021)
Column E shows the sum of columns A-D, while column G is the sum of columns E & F. (PNG)